2020
DOI: 10.1088/1742-6596/1517/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the accuracy of winnowing, rabin karp and knuth morris pratt algorithms in plagiarism detection applications

Abstract: The unethical behaviour of acts of plagiarism has been a disgrace in the educational realm. Using the internet, people can easily find articles or documents that are relevant to their current work, and simply duplicate the sentences or paragraphs without paraphrasing or giving correct citations. Such action falls into the area of plagiarism. In order to minimize the problem, especially in the educational field, it is necessary to develop plagiarism detection applications. The algorithm employed in the applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…The Cosine Similarity algorithm has also been used to check document similarity by producing a similarity level of 23% [39]. While the Knuth Morris Pratt algorithm provides an accuracy value of 9.20% to detect the similarity of two documents [25]. The comparison of the accuracy of the winnowing algorithm and several other algorithms used to check the similarity of the two documents can be seen in Table 9.…”
Section: Comparison Of Winnowing With Other Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cosine Similarity algorithm has also been used to check document similarity by producing a similarity level of 23% [39]. While the Knuth Morris Pratt algorithm provides an accuracy value of 9.20% to detect the similarity of two documents [25]. The comparison of the accuracy of the winnowing algorithm and several other algorithms used to check the similarity of the two documents can be seen in Table 9.…”
Section: Comparison Of Winnowing With Other Algorithmsmentioning
confidence: 99%
“…This algorithm can increase the efficiency of the document comparison process because of the concept of a window so that a hash value is formed, which is then used in the document matching process. In addition, the winnowing algorithm is also proven to provide a much greater accuracy value than Rabin Karp and Knuth Morris Pratt when used to detect plagiarism in documents [25].…”
Section: Introductionmentioning
confidence: 99%
“…Jaccard Coefficient digunakan untuk menghitung nilai similaritas pada algoritma Winnowing dan Dice's Coefficient pada algoritma Rabin-Karp. Hasil penelitian menunjukkan algoritma Winnowing lebih unggul daripada algoritma Rabin-Karp dan algoritma KMP karena algoritma Winnowing dapat mendeteksi plagiarisme yang kompleks [14].…”
Section: Pendahuluanunclassified
“…Meanwhile, in the Winnowing algorithm, fingerprints are determined by first grouping all hash values into windows based on a certain width. The rightmost minimum hash value obtained from each window is used as fingerprints [6], [7], [8], [9]. To prevent collisions in hash values, the Rolling Hash formula is used with the base number in the procedure using prime numbers [4], [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Winnowing algorithms as methods to identify word similarities between scientific work documents, the previous studies related to the application of both algorithms showed excellent results, either using in mono-language or multi-language forms and even using Chinese and Arabic letters [5], [9], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32].…”
Section: Introductionmentioning
confidence: 99%